(3GdJLGQI GdGdcJQhfjI hegGQGJ GdJShjb GdYdejs - (3GdSjO(B, (3Ydjhgs ((3eUQ(B:s (3OGQ GdGejf(B,s, 2002)
(3jJfGhd gPG GdcJGH(B: (3ChdkG (B: (3GdJLGQI GdEdcJQhfjI (B: (3Mhd JYQja GdJLGQI GdGdcJQhfjI (B: (3GdOhd GdfGejI hGdJWhQ aj GdJLGQI GdGdcJQhfjI (B: (3GdJLGQI GdGdcJQhfjI (B.. (3GdaQU hGdJMOjGJ (B((3Gdehba GdeUQj(B) : (3OhQ GdEfJQfJ aj GdJLGQI GdGdcJQhfjI (B: (3EOGQI GdJLGQI GdGdcJQhfjI (B: (3GdLhGfH GdbGfhfjI ddJHGOd GdEdcJQhfj ddHjGfGJ GdJLGQjI aj eLGd Jchjf GdYbhO hEKHGJ GdMbhb (B: (3dGFMI fXGe GdJLGQI GdGcJQhfjI GdYGdejI (B((3jhdjh (B1997) : (3TQcGJ JYed YHQ GdGfJQfJ (B: (3CfHGA hCNHGQ eJaQbI Yf GdJLGQI GdEdcJQhfjI (B: (3eYjGQ GdCee GdeJMOI aj GdJHGOd GdGdcJQhfj ddeYdheGJ (B: (3fehPL HQfGeL JOQjHj Mhd GdJLGQI GdEdcJQhfjI (B((3eHGOQI GdJLGQI GdGdcJQhfjI ddOhd GdYQHjI(B) : (3CbhGd ef GdEfJQfJ Mhd GdJLGQI GdEdcJQhfjI(B-(3KGfjkG (B: (3egGQGJ GdJShjb GdYdej (B: (3Gdeaghe GdJShjbj GdMOjK hGdHjFI GdJShjbjI (B: (3eGgjI GdJShjb (B: (3GdGJLGgGJ GacQjI dSdhc GdEOGQI MjGd GdeTJQj (B: (3CSS JWHjbjI (B: (3UYhHGJ JWHjbjI Gdeaghe GdMOjK ddJShjb aj efTBJ GdEfJGL GdUfGYj hCSGdjH GdYdGL GdefGSHI (B: (3HMhK GdJShjb (B: (3JYQja HMhK GdJShjb (B: (3NWhGJ GdHMhK GdHOGFjI (B: (3fehPL Yedj aj HMhK GdJShjb (B: (3SjGSGJ WQb hefGaP GdJhRjY (B: (3GSJQGJjLjI GdJQhjL hSdhc GdeSJgdc (B: (3echfGJ GdeRjL GdJQhjLj (B: (3fehPL GdGJUGdGJ GdJShjbjI(B.s
(3HjHdjhZQGajG (B: (3U(B.260s
Keywords: (3GdJLGQI GdGdcJQhfjIs; (3GdJShjbs